2022
DOI: 10.1039/d1ma00663k
|View full text |Cite
|
Sign up to set email alerts
|

Structural alterations on the TEMPO scaffold and their impact on the performance as active materials for redox flow batteries

Abstract: Trimethylammonium-2,2,6,6-tetramethylpiperidine-1-oxyl chlorid (TMA-TEMPO) has been intensively studied for the usage in aqueous organic redox flow batteries. A straightforward synthesis, a reliable electrochemistry, fast kinetics and high cyc¬ling stability are the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…This value can be considered as high and suggests that larger reaction times will yield quantitative yields. This is in good accordance with the literature, where often reaction times of one to five days, depending on the structure, are proposed for obtaining high yields [4,23] . As highly concentrated hydrogen peroxide solutions can represent a potential risk in large‐scale processes, the reaction was repeated exemplarily with six and ten equivalents of a 35 % H 2 O 2 solution.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This value can be considered as high and suggests that larger reaction times will yield quantitative yields. This is in good accordance with the literature, where often reaction times of one to five days, depending on the structure, are proposed for obtaining high yields [4,23] . As highly concentrated hydrogen peroxide solutions can represent a potential risk in large‐scale processes, the reaction was repeated exemplarily with six and ten equivalents of a 35 % H 2 O 2 solution.…”
Section: Resultssupporting
confidence: 86%
“…This is in good accordance with the literature, where often reaction times of one to five days, depending on the structure, are proposed for obtaining high yields. [4,23] As highly concentrated hydrogen peroxide solutions can represent a potential risk in large-scale processes, the reaction was repeated exemplarily with six and ten equivalents of a 35 % H 2 O 2 solution. For six equivalents, a DoO of 85 % was obtained at room temperature.…”
Section: Sodium Tungstatementioning
confidence: 99%
See 1 more Smart Citation
“…Both the TEMPOAmide and the PTMAm investigated as RM and RT in this study, respectively, are available through straight forward lab-scale synthesis. [12,14] They are structurally closely related, as both show an amide bond in the 4-position of the redox-active TEMPO-moiety. In case of the PTMAm, the amide connects the TEMPO to the crosslinked polymer backbone, that mediates the insolubility while maintaining the hydrophilic character of the amide bond.…”
Section: Resultsmentioning
confidence: 99%
“…[13] As this chemical modification also leads to a change of the standard potential of the RT, another N,N,N-trimethyl-2-oxo-2-[(2,2,6,6-tetramethylpiperidin-4-yloxyl)amino]ethan-1ammonium chloride (TEMPOAmide) was investigated as RM, since it was presented earlier as a stable TEMPO-based redoxactive material for aqueous organic redox flow batteries. [14] Flow batteries have been constructed and the material combination was evaluated in a fully operating quasi-symmetrical flow battery setup, where the non-capacity limiting side contained a large amount of TMATEMPO-based electrolyte and no RT. Furthermore, a new figure of merit is mathematically derived in this study based on the charge transfer in the flow cell and the state-of-charge (SOC) change of the RM and it is demonstrated that the SOC change of the RT can be inferred from the data.…”
Section: Introductionmentioning
confidence: 99%